Distinguishing Features of Adolescents With Undiagnosed Infectious Tuberculosis Attending a Pediatric Emergency Department. (25th August 2021) - Al Dubisi, Fatimah; Harvey, Gregory; Ostrow, Olivia; Lam, Ray; Science, Michelle; Kitai, Ian
Abstract: More than 10 days of fever or 13 days of cough differentiated adolescent patients presenting to a pediatric emergency department with infectious tuberculosis (TB) from most patients with pneumonia. Upper lobe involvement was significantly more common in patients with TB. Symptom- and radiograph-based algorithms could minimize TB exposure and aid diagnosis.